Challenges of Collection Management: Analysis, Staffing, and Space. Issue 1 (1st June 2020) - Adams, Lisa; Church, Melanie; Hanson, Michael; Larsen, Ali
ABSTRACT: Academic libraries face limitations of space, staffing, budget, and other factors, but still must maintain their collections responsibly. Collection maintenance with the goal of reclaiming space requires both solid data analysis and sufficient staff to execute projects. Presenters with perspectives from Siena College, Rockhurst University, and Sam Houston State University discuss their experiences in facing the challenges of analyzing data and managing workflows for current and potential removal projects. An OCLC Regional Library Services Manager describes their product Green Glass and its involvement with the project at Sam Houston State University.